Do museu como espaço ao museu como lugar de múltiplas interlocuções: os museus universitários e as coleções do povo Bororo - Silva, Jocenaide Maria Rossetto (2013)
The pages of history I propose to build are located in the dimensions of Social and Cultural History, in their fields related to museums, as the theories of history become integrated to interdisciplinary dialogues with other theories (museology and communication). For that, both the research approaches and the methodologies of analysis fit into material culture, imagetic and textual sources, having as field of observation and investigation (in loco and virtual) the museological spaces (technical reserve, exhibition and educational sector), in the Museum of Archaeology and Ethnology - University of São Paulo - USP (São Paulo, SP), in Dom Bosco Museum of Cultures Dom Bosco Catholic University-UCDB (Campo Grande, MS); in the Cultural Center Padre Rodolfo Lunkenbein Aldeia de Meruri , connected to Dom Bosco Museum of Cultures Dom Bosco Catholic University-UCDB (Campo Grande, MS); and in Rondon Museum in the Federal University of Mato Grosso - UFMT (Cuiabá, MT). This thesis discusses the expectations for museum modernization by means of new information technologies, announcing new paradigms that characterize contemporary times. Thus, I argue that such changes unfold themselves and resignify the space-museum. The communicational relations which I refer to were investigated into three dimensions: 1) in the context of the museum and its surroundings (community, city and Indian settlement); 2) in the context of the multiple technologies which set new paradigms to information, and 3) to whom the museums represent in their collections, of which I opt for the sampling of the Bororo Indian s collections of artifacts. The arguments put and results are presented in three parts, Part I being related to the social and cultural history of the surveyed university museums of ethnology, emphasizing the composition of the Bororo s collections of artifacts, their conservation, exhibitions and communicational perspectives. Part II concerns to the museal planned action for Bororo s culture communication, through museological and patrimonial education; in Part III, I consider tangible culture, i.e., the objects kept exhibited in university museums and, from them, I extend researches to intangible cultural references, as a way to contribute to the Bororo s written, social and cultural history. I conclude my thesis by arguing for changing the notion of space-museum by the one of place-museum, by means of communication and integration of new technologies, in particular the World Wide Web